Perancangan Desain Komunikasi Visual Dalam Bentuk Kampanye Instagram “Apresiasi Kerja Desainer” - Nurul Aqmarina Ardani (AKSA: Jurnal Desain Komunikasi Visual, 2018)
The working fee of graphic designers is still being felt to be very low because there is no appreciation from business owners and also from the public. To increase the appreciation, there have been many campaigns regarding the appreciation of the work of graphic designers on social media Instagram with positive reviews, but many graphic designers said that there is still no change. The author then tried to analyze some of the shortcomings of these campaigns and tried to add new strategies. The author hoped that the new campaign with the new communication strategy could deliver better message to the business owners and public. The author used brand audit, brand awareness, and brand management theory from Keller (2013), Kartajaya (2016) and also social movement theory from Aspen Institute Roundtable (2013) to do the campaign strategy researches. The outcome of this artwork is a conceptual campaign with a complete communication strategy guide. Keywords